A battery shell for energy storage and production method thereof
By preparing an aluminum alloy shell under a rare gas atmosphere and performing multiple heat treatments and hot stamping treatments, the problem of thinning of the battery shell weight and thickness is solved, and the lightweight and high energy density of the battery shell is achieved, which improves the Overall performance of the battery.
Patent Information
- Application Number
- CN202411617320.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-13
AI Technical Summary
While reducing weight and thickness, the existing battery case cannot meet the basic requirements of the battery case, resulting in limited energy density improvement.
Using a production method of battery shell for energy storage, by mixing molten aluminum alloy raw materials under a rare gas atmosphere, performing multiple heat treatment and hot stamping treatment, an aluminum alloy shell with a density of about 2.7 g/cm3 is prepared, and the wall is Thickness is less than 1mm.
It realizes the lightweight and high energy density of the battery case, improves the overall performance of the battery, and has high mechanical properties, thermal stability and corrosion resistance.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a battery casing for energy storage and a production method thereof. Background Art
[0002] With the popularity of new energy vehicles, the capacity of new energy vehicle batteries as core components has become a research focus. At present, there are two main ways to improve the energy density of batteries: one is to increase the specific energy of single cells; the other is to make the battery pack structure lightweight. However, increasing the specific energy of single cells is technically difficult, with a long R&D cycle and large capital investment; in contrast, making the battery pack structure lightweight is easier to achieve, and the lightweight structure of the battery pack is mainly reflected in the lightweight battery shell.
[0003] The lightweighting of battery shells mainly involves two ways: reducing the weight and reducing the thickness of the shell while meeting the basic requirements of the shell. At present, the shell weight is reduced by adjusting the raw material components and ratios of the shell materials, and the shell thickness is reduced by stamping forming methods, that is, using a punch press and a hydraulic press to punch out the aluminum plate, stretch it through multiple passes, and temper it to remove stress. However, the current battery shells and their production methods cannot both reduce the shell weight and reduce the thickness while meeting the basic requirements of the battery shell. Summary of the invention
[0004] In order to solve the above problems, the present application proposes a battery shell for energy storage and a production method thereof. The battery shell material produced by the production method for energy storage is light (density 2.7g / cm 3 The shell wall thickness is less than 1mm, which makes the battery shell lightweight, further lightweight the battery pack structure and improves the energy density of the battery.
[0005] This application is implemented through the following technical solutions:
[0006] In a first aspect, the present application provides a method for producing a battery housing for energy storage, comprising the following steps:
[0007] S1. In a rare gas atmosphere, a molten aluminum alloy raw material is mixed and kept at 680°C to 730°C for 2h to 5h to obtain an aluminum alloy melt, wherein the aluminum alloy melt is composed of the following components by mass fraction: 7% to 15% lithium, 0.6% to 0.8% beryllium, 0.5% to 0.8% magnesium, 0.08% to 0.11% indium, 0.09% to 0.2% nickel, 0.2% to 0.4% silicon, 1.2% to 2% rare earth metal, 0.02% to 0.03% boron, and the balance is aluminum and unavoidable impurities;
[0008] S2. At a pressure of 2MPa~5MPa, the aluminum alloy melt is injected into the energy storage battery housing mold and maintained at a pressure of 10s~60s;
[0009] S3. The aluminum alloy shell after pressure maintenance is subjected to three-stage heat treatment to obtain a pretreated aluminum alloy shell;
[0010] The three-stage heat treatment includes:
[0011] The first stage of heat treatment: cooling to 150℃~230℃ at a cooling rate of 50℃ / s~100℃ / s; homogenization heat treatment for 12h~24h;
[0012] The second heat treatment: cool to -10°C~0°C at a cooling rate of 50°C / s~100°C / s, then heat to 150°C~230°C at a heating rate of 25°C / s~30°C / s and keep warm for 20min~80min;
[0013] The third heat treatment: cooling to -150℃~-80℃ at a cooling rate of 120℃ / s~180℃ / s, then heating to 100℃~180℃ at a heating rate of 125℃ / s~180℃ / s and keeping warm for 20min~80min;
[0014] S4. Hot stamping the pretreated aluminum alloy shell and then quenching and cooling it to obtain a battery shell for energy storage.
[0015] In some possible implementations, the production method further includes the following steps:
[0016] The pretreated aluminum alloy shell is subjected to aging treatment after hot stamping, the temperature is 120° C. to 180° C., and the time is 8 h to 20 h.
[0017] In some possible implementations, in the hot stamping step, the temperature is 190° C. to 220° C., and the holding time is 5 s to 20 s.
[0018] In some possible implementations, the rare gas is at least one of helium, neon, and argon.
[0019] In some possible implementations, in the hot stamping step, the hot stamping is performed more than once.
[0020] In some possible implementations, the rare earth metal includes at least one of lanthanum (La) and cerium (Ce).
[0021] In a second aspect, the present application provides a battery shell for energy storage, which is manufactured using the production method of the battery shell for energy storage provided in the present application.
[0022] The present application provides a battery housing for energy storage and a production method thereof, which, compared with the prior art, has at least the following beneficial technical effects:
[0023] (1) The production method of the energy storage battery shell provided in the present application is that, in a rare gas atmosphere, it is not easy to introduce other non-metallic impurities or metal oxidation into the prepared aluminum alloy melt, thereby ensuring the purity of the aluminum alloy melt; the temperature is kept at 680°C to 730°C for 2h to 5h, so that the raw material components in the aluminum alloy melt are evenly mixed, the grains are refined, the fluidity of the aluminum alloy melt is improved, and the subsequent casting and molding of the aluminum alloy melt is facilitated.
[0024] (2) In the production method of the energy storage battery shell provided in the present application, beryllium, silicon, and rare earth metals in the aluminum alloy melt improve the fluidity of the aluminum alloy, making it easier for the aluminum alloy melt to fill the energy storage battery shell mold during the casting process, reducing the generation of defects such as pores and shrinkage holes, and making the liquid melt evenly distributed and then solidified.
[0025] (3) The production method of the energy storage battery shell provided in the present application applies pressure and maintains pressure when injecting the aluminum alloy melt into the energy storage battery shell mold, which can improve the density and strength of the energy storage battery shell.
[0026] (4) The production method of the energy storage battery shell provided in the present application adopts a three-stage heat treatment, wherein the second and third heat treatments adopt a process of rapid cooling to rapid heating followed by short-term heat preservation, which can significantly refine the grains and enhance the mechanical properties (tensile strength, ductility and toughness) of the aluminum alloy; the heat treatment can also form a metal oxide film on the surface of the shell, thereby improving the corrosion resistance of the energy storage battery shell.
[0027] (5) The production method of the energy storage battery shell provided in the present application can further refine the grain size of the aluminum alloy shell by hot stamping, thereby minimizing the weight of the energy storage battery shell product while maintaining the performance of the energy storage battery shell product, thereby improving the energy density of the battery from the perspective of the battery shell structure.
[0028] (6) In the production method of the energy storage battery shell provided in the present application, aging treatment can promote the formation and stabilization of the hard phase in the aluminum alloy, thereby improving the strength and hardness of the material.
[0029] (7) The energy storage battery shell produced by the production method of the energy storage battery shell provided in the present application has high mechanical properties, thermal stability and corrosion resistance.
[0030] (8) The energy storage battery shell provided in this application contains lightweight metal elements such as beryllium, magnesium, and indium in the aluminum alloy, which reduces the weight of the battery shell, and its grain structure is dense, with a grain size of less than 50 μm. When the wall thickness of the energy storage battery shell is less than 1 mm, its thermal stability, strength, toughness and other properties still meet the requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0032] Figure 1 A schematic flow chart of a method for producing a battery casing for energy storage according to an embodiment of the present application.
[0033] The purpose, features and advantages of this figure will be further described in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0035] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in the field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.
[0036] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.
[0037] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution, and all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0038] The first aspect of the present application provides a method for producing a battery housing for energy storage, as shown in the attached Figure 1 As shown, the following steps are included:
[0039] S1. In a rare gas atmosphere, molten aluminum alloy raw materials are mixed and kept at 680°C~730°C for 2h~5h to obtain an aluminum alloy melt, which is composed of the following components in mass fractions: 7%~15% lithium, 0.6%~0.8% beryllium, 0.5%~0.8% magnesium, 0.08%~0.11% indium, 0.09%~0.2% nickel, 0.2%~0.4% silicon, 1.2%~2% rare earth metals, 0.02%~0.03% boron, and the balance is aluminum and unavoidable impurities.
[0040] S2. At a pressure of 2MPa~5MPa, inject the aluminum alloy melt into the energy storage battery shell mold and maintain the pressure for 10s~60s.
[0041] S3. The aluminum alloy shell after pressure maintenance is subjected to three-stage heat treatment to obtain a pretreated aluminum alloy shell;
[0042] The three-stage heat treatment includes:
[0043] The first stage of heat treatment: cooling to 150℃~230℃ at a cooling rate of 50℃ / s~100℃ / s; homogenization heat treatment for 12h~24h;
[0044] The second heat treatment: cool to -10°C~0°C at a cooling rate of 50°C / s~100°C / s, then heat to 150°C~230°C at a heating rate of 25°C / s~30°C / s and keep warm for 20min~80min;
[0045] The third stage of heat treatment: cool to -150℃~-80℃ at a cooling rate of 120℃ / s~180℃ / s, then heat to 100℃~180℃ at a heating rate of 125℃ / s~180℃ / s and keep warm for 20min~80min.
[0046] S4. The pretreated aluminum alloy shell is hot stamped and then quenched and cooled to obtain a battery shell for energy storage.
[0047] The production method of the energy storage battery shell provided in the embodiment of the present application is that in a rare gas atmosphere, it is not easy to introduce other non-metallic impurities or metal oxidation into the prepared aluminum alloy melt, thereby ensuring the purity of the aluminum alloy melt; the raw material components in the aluminum alloy melt are evenly mixed, and the grains are refined, the fluidity of the aluminum alloy melt is improved, and it is beneficial to the subsequent casting of the aluminum alloy melt. In the aluminum alloy melt, beryllium, silicon, and rare earth metals improve the fluidity of the aluminum alloy, so that the aluminum alloy melt is easier to fill the energy storage battery shell mold during the casting process, reduce the generation of defects such as pores and shrinkage holes, and make the liquid melt uniformly distributed and solidified. When the aluminum alloy melt is injected into the energy storage battery shell mold, pressurization and pressure maintenance can improve the density and strength of the energy storage battery shell. The three-stage heat treatment can significantly refine the grains and enhance the mechanical properties (tensile strength, ductility and toughness) of the aluminum alloy; the heat treatment can also form a metal oxide film on the shell surface to improve the corrosion resistance of the energy storage battery shell. Hot stamping can further refine the grain size of the aluminum alloy shell, while maintaining the performance of the energy storage battery shell product, and minimize the weight of the energy storage battery shell product, thereby improving the energy density of the battery from the battery shell structure. Aging treatment can promote the formation and stabilization of the hard phase in the aluminum alloy, thereby improving the strength and hardness of the material. The energy storage battery shell produced by the production method of the energy storage battery shell provided in the present application has high mechanical properties, thermal stability and corrosion resistance.
[0048] In the embodiment, the mass fraction of lithium is 7% to 15%, which can be 7%, 9%, 10%, 13%, 15% and other typical but non-limiting mass fractions or a range between any two mass fractions. In this case, the density of lithium is only 0.534 g / cm 3 , and aluminum can work together to reduce the density of aluminum alloys, increase the specific strength of aluminum alloys, enhance the fatigue resistance of aluminum alloys, increase the elastic modulus of aluminum alloys, and improve the corrosion resistance of aluminum alloys. In addition, lithium can also refine the grains of aluminum alloys and increase the density of the grain structure of aluminum alloys.
[0049] In the embodiment, the mass fraction of beryllium is 0.6% to 0.8%, which can be a typical but non-restrictive mass fraction such as 0.6%, 0.7%, 0.8%, or a range between any two mass fractions. In this case, beryllium and aluminum form a strengthening phase to improve the strength and hardness of the aluminum alloy; beryllium can also limit grain growth, refine the grains of the aluminum alloy, improve its microstructure, improve the microstructural stability of the alloy, and further improve the mechanical properties of the aluminum alloy; beryllium and aluminum form a dense oxide film to improve the corrosion resistance of the aluminum alloy. In addition, during the casting process of the aluminum alloy, beryllium significantly reduces the surface tension of the aluminum alloy, reduces the formation of pores and shrinkage cavities, and thus improves the casting quality of the aluminum alloy.
[0050] In the embodiment, the mass fraction of magnesium is 0.5% to 0.8%, which may be 0.5%, 0.6%, 0.7%, 0.8% or any other typical but non-limiting mass fractions or a range between any two mass fractions. In this case, the density of magnesium is about 1.8 g / cm 3 , which has significant lightweight properties, improves the specific strength of the aluminum alloy, thereby reducing the weight of the battery casing and making the battery casing lightweight.
[0051] In the embodiment, the mass fraction of indium is 0.08% to 0.11%, which can be a typical but non-limiting mass fraction such as 0.08%, 0.09%, 0.11%, or a range between any two mass fractions. In this case, indium can enhance the strength, rigidity and impact resistance of the aluminum alloy, and improve the corrosion resistance of the aluminum alloy.
[0052] In the embodiment, the mass fraction of nickel is 0.09% to 0.2%, which may be 0.09%, 0.1%, 0.15%, 0.2%, or any other typical but non-limiting mass fractions or a range between any two mass fractions. In this case, nickel can improve the tensile strength and hardness of the aluminum alloy.
[0053] In the embodiment, the mass fraction of silicon is 0.2% to 0.4%, which can be a typical but non-restrictive mass fraction such as 0.2%, 0.3%, 0.4%, or a range between any two mass fractions. In this case, the silicon element can form a layer of SiO2 protective film to improve the corrosion resistance of the aluminum alloy. Silicon can improve the fluidity of the aluminum alloy, making it easier for the aluminum alloy to fill every corner of the mold during the casting process, reducing the generation of defects such as pores and shrinkage cavities.
[0054] In the embodiment, the mass fraction of the rare earth metal is 1.2% to 2%, which can be 1.2%, 1.5%, 1.9%, 2%, etc., which are typical but non-limiting mass fractions, or a range between any two mass fractions. In this case, the rare earth metal significantly improves the strength, toughness and plasticity of the aluminum alloy, and can also improve the fluidity of the aluminum alloy, making it easier for the aluminum alloy to fill the mold during the casting process.
[0055] In the embodiment, the mass fraction of boron is 0.02% to 0.03%, which can be a typical but non-limiting mass fraction such as 0.02%, 0.03%, or a range between any two mass fractions. In this case, boron can refine the grains of the aluminum alloy, stabilize the microstructure of the aluminum alloy in a high temperature environment, and enhance heat resistance.
[0056] In the embodiment, after mixing the molten aluminum alloy raw materials, they are kept at 680℃~730℃ for 2h~5h, so that the raw material components in the aluminum alloy melt are evenly mixed, the grains are refined, and the fluidity of the aluminum alloy melt is improved; when the aluminum alloy melt is injected into the energy storage battery housing mold, the density and strength of the aluminum alloy can be improved. Among them, the temperature is 680℃~730℃, which can be a typical but non-restrictive temperature such as 680℃, 700℃, 730℃, or a range between any two temperatures; the insulation time is 2h~5h, which can be a typical but non-restrictive insulation time such as 2h, 3h, 4h, 5h, or a range between any two insulation times.
[0057] In the embodiment, the pressure is 2 MPa to 5 MPa, and can be typical but non-limiting pressures such as 2 MPa, 3 MPa, 4 MPa, 5 MPa, or a range between any two pressures.
[0058] In the embodiment, the battery housing mold for energy storage is an existing mold in the art and is not particularly limited in the embodiment of the present application.
[0059] In the embodiment, the holding time is 10s to 60s, which may be a typical but non-limiting holding time such as 10s, 20s, 40s, 60s, or a range between any two holding times.
[0060] In the embodiment, in the first stage of heat treatment, the temperature of the homogenization heat treatment is 150°C to 230°C, which can be a typical but non-limiting temperature such as 150°C, 180°C, 230°C, or a range between any two temperatures.
[0061] In the embodiment, in the second stage heat treatment, the cooling rate is 50°C / s to 100°C / s, which can be typical but non-limiting cooling rates such as 50°C / s, 80°C / s, 100°C / s, or a range between any two cooling rates.
[0062] In the embodiment, in the second stage heat treatment, the cooling temperature is -10°C to 0°C, which can be typical but non-limiting cooling temperatures such as -10°C, -5°C, 0°C, or a range between any two cooling temperatures.
[0063] In the embodiment, in the second stage heat treatment, the heating rate is 25°C / s to 30°C / s, which can be a typical but non-limiting heating rate such as 25°C / s, 28°C / s, 30°C / s, or a range between any two heating rates.
[0064] In the embodiment, in the second stage heat treatment, the heating temperature is 150°C to 230°C, which can be a typical but non-limiting heating temperature such as 150°C, 180°C, 230°C, or a range between any two heating temperatures.
[0065] In the embodiment, in the third stage heat treatment, the cooling rate is 120°C / s to 180°C / s, which can be a typical but non-limiting cooling rate such as 120°C / s, 150°C / s, 180°C / s, or a range between any two cooling rates.
[0066] In the embodiment, in the third stage heat treatment, the cooling temperature is -150°C to -80°C, which can be typical but non-limiting cooling temperatures such as -150°C, -100°C, 80°C, or a range between any two cooling temperatures.
[0067] In the embodiment, in the third stage of heat treatment, the heating rate is 125°C / s to 180°C / s, which can be a typical but non-limiting heating rate such as 125°C / s, 150°C / s, 180°C / s, or a range between any two heating rates.
[0068] In the embodiment, in the third stage heat treatment, the heating temperature is 100°C to 180°C, which can be a typical but non-limiting heating temperature such as 100°C, 150°C, 180°C, or a range between any two heating temperatures.
[0069] In some specific embodiments, in the above S1, the rare gas is at least one of helium, neon, and argon. In this case, the rare gas as a protective atmosphere does not chemically react with the aluminum alloy raw material, and can provide a gaseous environment required for melting the raw material, thereby indirectly reducing the difficulty of production.
[0070] In some specific embodiments, in the above S1, the rare earth metal includes at least one of lanthanum (La) and cerium (Ce). In this case, the melting point of lanthanum (La) and / or cerium (Ce) is relatively low, which reduces the production cost of the aluminum alloy.
[0071] In some specific embodiments, in the above S1, the aluminum alloy melt consists of the following components in mass fractions:
[0072] 81%~90% aluminum, 7%~15% lithium, 0.6%~0.8% beryllium, 0.5%~0.8% magnesium, 0.08%~0.11% indium, 0.09%~0.2% nickel, 0.2%~0.4% silicon, 1.2%~2% rare earth metals, 0.02%~0.03% boron.
[0073] In the embodiment, the mass fraction of aluminum is 81% to 90%, which can be 81%, 85%, 87%, 90% or other typical but non-limiting mass fractions or a range between any two mass fractions. In this case, the density of aluminum is about 2.7 g / cm 3, which has significant lightness and can significantly reduce the density of aluminum alloy, thereby reducing the weight of the battery shell and making the battery shell lightweight. In addition, aluminum can naturally form a dense aluminum oxide film in the air, which can effectively prevent further oxidation of aluminum, thus giving aluminum alloy good corrosion resistance.
[0074] In some embodiments, in the above S3, in the first stage of heat treatment, the temperature is lowered to 150°C~230°C at a cooling rate of 50°C / s~100°C / s; the homogenization heat treatment time is 12h~24h. In this case, grain refinement can be promoted and the mechanical properties (tensile strength, ductility and toughness) of the aluminum alloy can be enhanced; the homogenization heat treatment forms an oxide film on the shell surface to improve the corrosion resistance of the aluminum alloy.
[0075] In some embodiments, in the above S3, in the second stage of heat treatment, the holding time is 20min~80min, and in the exemplary example, it can be a typical but non-limiting holding time such as 20min, 50min, 80min, or a range between any two holding times. In some embodiments, in the above S3, in the third stage of heat treatment, the holding time is 20min~80min, and in the exemplary example, it can be a typical but non-limiting holding time such as 20min, 50min, 80min, or a range between any two holding times. In this case, two stages of low-temperature insulation, combined with homogenous heat treatment, can increase the solid solution phase in the aluminum alloy, thereby improving the strength and hardness of the aluminum alloy.
[0076] In some embodiments, in the above S4, in the hot stamping step, the temperature is 190°C to 220°C, and in the exemplary example, it can be a typical but non-limiting temperature such as 190°C, 200°C, 220°C, or a range between any two temperatures. In some embodiments, in the above S4, in the hot stamping step, the holding time is 5s to 20s, and in the exemplary example, it can be a typical but non-limiting time such as 5s, 10s, 15s, 20s, or a range between any two times. In this case, hot stamping can further refine the grain size of the aluminum alloy shell, while maintaining the performance of the energy storage battery shell product, it can minimize the weight of the energy storage battery shell product, thereby improving the energy density of the battery from the battery shell structure.
[0077] In some embodiments, in the above S4, in the hot stamping step, the number of hot stamping is one or more.
[0078] In some embodiments, in the above S4, in the hot stamping step, the number of hot stamping is 2 to 3 times.
[0079] In some embodiments, in the above S4, the production method further comprises the following steps:
[0080] The pre-treated aluminum alloy shell is subjected to aging treatment after hot stamping. In some specific embodiments, the temperature of the aging treatment is 120°C to 180°C. In the exemplary embodiment, it can be a typical but non-limiting temperature such as 120°C, 150°C, 180°C, 200°C, or a range between any two temperatures. In some specific embodiments, the time of the aging treatment is 8h to 20h. In the exemplary embodiment, it can be a typical but non-limiting time such as 8h, 10h, 12h, 16h, 20h, or a range between any two times. In this case, aging treatment after hot stamping can reduce the stress generated inside the alloy during hot stamping, strengthen the metal material, and improve the mechanical strength and hardness of the alloy. It should be noted that when the number of hot stamping is more than 2 times, an aging treatment is performed for each hot stamping to eliminate the internal stress generated in the alloy due to hot stamping. In some embodiments, in the above S4, in the quenching cooling step, the cooling rate is 20°C / s to 50°C / s, and in an exemplary embodiment, it can be a typical but non-limiting cooling rate such as 20°C / s, 30°C / s, 40°C / s, 50°C / s, or a range between any two cooling rates. At this cooling rate, the stress inside the aluminum alloy can be reduced, and the mechanical properties and thermal stability of the aluminum alloy can be improved.
[0081] In some specific embodiments, a method for producing a battery housing for energy storage is provided, the steps of which are as follows:
[0082] S10. In a rare gas atmosphere, molten aluminum alloy raw materials are mixed and kept warm at 680°C~730°C for 2h~5h to obtain an aluminum alloy melt, which is composed of the following components in mass fractions: 7%~15% lithium, 0.6%~0.8% beryllium, 0.5%~0.8% magnesium, 0.08%~0.11% indium, 0.09%~0.2% nickel, 0.2%~0.4% silicon, 1.2%~2% rare earth metals, 0.02%~0.03% boron, and the remainder is aluminum and unavoidable impurities.
[0083] S20. At a pressure of 2MPa~5MPa, inject the aluminum alloy melt into the energy storage battery shell mold and maintain the pressure for 10s~60s.
[0084] S30. The aluminum alloy shell after pressure maintenance is subjected to three-stage heat treatment to obtain a pretreated aluminum alloy shell;
[0085] The three-stage heat treatment includes:
[0086] The first stage of heat treatment: homogenization heat treatment at 150℃~230℃ for 12h~24h;
[0087] The second heat treatment: cool to -10°C~0°C at a cooling rate of 50°C / s~100°C / s, then heat to 150°C~230°C at a heating rate of 25°C / s~30°C / s and keep warm for 20min~80min;
[0088] The third stage of heat treatment: cool to -150℃~-80℃ at a cooling rate of 120℃ / s~180℃ / s, then heat to 100℃~180℃ at a heating rate of 125℃ / s~180℃ / s and keep warm for 20min~80min.
[0089] S40. hot stamping the pretreated aluminum alloy shell at a temperature of 190°C to 220°C for 5s to 20s.
[0090] S50. Perform aging treatment on the pretreated aluminum alloy shell at a temperature of 120° C. to 180° C. for 8 h to 20 h to obtain an aluminum alloy shell.
[0091] S60. Quench and cool the aluminum alloy shell at a cooling rate of 20°C / s to 50°C / s to obtain a battery shell for energy storage.
[0092] In some other specific embodiments, a method for producing a battery housing for energy storage is provided, and the steps are as follows:
[0093] S11. In a rare gas atmosphere, molten aluminum alloy raw materials are mixed and kept at 680°C~730°C for 2h~5h to obtain an aluminum alloy melt, which is composed of the following components in mass fractions: 7%~15% lithium, 0.6%~0.8% beryllium, 0.5%~0.8% magnesium, 0.08%~0.11% indium, 0.09%~0.2% nickel, 0.2%~0.4% silicon, 1.2%~2% rare earth metals, 0.02%~0.03% boron, and the remainder is aluminum and unavoidable impurities.
[0094] S21. At a pressure of 2MPa~5MPa, inject the aluminum alloy melt into the energy storage battery shell mold and maintain the pressure for 10s~60s.
[0095] S31. The aluminum alloy shell after pressure maintenance is subjected to three-stage heat treatment to obtain a pretreated aluminum alloy shell;
[0096] The three-stage heat treatment includes:
[0097] The first stage of heat treatment: homogenization heat treatment at 150℃~230℃ for 12h~24h;
[0098] The second heat treatment: cool to -10°C~0°C at a cooling rate of 50°C / s~100°C / s, then heat to 150°C~230°C at a heating rate of 25°C / s~30°C / s and keep warm for 20min~80min;
[0099] The third stage of heat treatment: cool to -150℃~-80℃ at a cooling rate of 120℃ / s~180℃ / s, then heat to 100℃~180℃ at a heating rate of 125℃ / s~180℃ / s and keep warm for 20min~80min.
[0100] S41. The pretreated aluminum alloy shell is hot stamped at a temperature of 190°C to 220°C for 5s to 20s, and then aged at a temperature of 120°C to 180°C for 8h to 20h.
[0101] S51. Repeat S41 once or twice.
[0102] S61. Quench and cool the pretreated aluminum alloy shell at a cooling rate of 20°C / s to 50°C / s to obtain a battery shell for energy storage.
[0103] A second aspect of an embodiment of the present application provides a battery shell for energy storage, including a battery shell for energy storage produced by the production method of a battery shell for energy storage provided in an embodiment of the present application.
[0104] The energy storage battery shell provided in the embodiment of the present application includes the energy storage battery shell produced by the production method of the energy storage battery shell provided in the present application, and its aluminum alloy contains light metal elements such as beryllium, magnesium, and indium, which reduces the weight of the battery shell, and its grain structure is dense, and the grain size is less than 50μm. When the wall thickness of the energy storage battery shell is less than 1mm, its thermal stability, strength, and toughness still meet the requirements. The energy storage battery shell provided in the embodiment of the present application has high mechanical properties, thermal stability, and corrosion resistance.
[0105] In some embodiments, the wall thickness of the energy storage battery housing is 0.6 mm to 0.9 mm. In the exemplary embodiment, it can be 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, etc., which are typical but non-limiting thicknesses, or a range between any two thicknesses. In this case, the battery housing achieves a lightweight structure, thereby improving the battery energy density structurally.
[0106] In some embodiments, the average grain size of the aluminum alloy in the energy storage battery housing is 32 μm to 39 μm. In an exemplary embodiment, the average grain size may be 32 μm, 34 μm, 37 μm, 39 μm, or any range between two average grain sizes. In this case, the tensile strength, yield strength, and toughness of the aluminum alloy are significantly improved.
[0107] In some embodiments, the yield strength of the energy storage battery shell is 291MPa~319MPa. In the exemplary embodiment, it can be 291MPa, 293MPa, 295MPa, 298MPa, 301MPa, 303MPa, 304MPa, 305MPa, 308MPa, 312MPa, 315MPa, 319MPa, etc. Typical but non-limiting yield strengths or ranges between any two yield strengths. In this case, the wall thickness of the energy storage battery shell can be less than 1mm, which realizes the lightweight of the battery shell, further lightweight the structure of the battery pack, and improves the energy density of the battery.
[0108] The following is further described in conjunction with specific embodiments.
[0109] Example 1
[0110] Example 1 proposes a method for producing a battery housing for energy storage, the steps are as follows:
[0111] S1. In a helium atmosphere, the aluminum alloy raw materials are mixed and melted, and the mixture is kept at 700°C for 2.5 hours to obtain an aluminum alloy melt. The aluminum alloy melt is composed of the following components by mass fraction: 83.83% aluminum, 12.45% lithium, 0.78% beryllium, 0.8% magnesium, 0.09% indium, 0.17% nickel, 0.35% silicon, 1.5% lanthanum and 0.03% boron.
[0112] S2. At a pressure of 3 MPa, inject the aluminum alloy melt into the energy storage battery shell mold and maintain the pressure for 30 seconds.
[0113] S3. The aluminum alloy shell after pressure maintenance is subjected to three-stage heat treatment to obtain a pretreated aluminum alloy shell;
[0114] The three-stage heat treatment is:
[0115] The first stage of heat treatment: cooling down to 200℃ at a cooling rate of 60℃ / s, and homogenizing heat treatment at 200℃ for 16h;
[0116] The second heat treatment: cooling to -8°C at a cooling rate of 80°C / s, then heating to 200°C at a heating rate of 30°C / s and keeping at this temperature for 60 min;
[0117] The third heat treatment: cool to -100°C at a cooling rate of 150°C / s, then heat to 150°C at a heating rate of 165°C / s and keep warm for 50 min.
[0118] S4. hot stamping the pretreated aluminum alloy shell at a temperature of 200°C for 10s; quenching and cooling the aluminum alloy shell at a cooling rate of 30°C / min to obtain a battery shell for energy storage.
[0119] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.65 mm.
[0120] Example 2
[0121] Example 2 proposes a method for producing a battery shell for energy storage. The steps are basically the same as those in Example 1, except that the S4 pretreated aluminum alloy shell is subjected to aging treatment after hot stamping treatment, and the aging treatment temperature is 150°C and the time is 12 hours.
[0122] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.67 mm.
[0123] Example 3
[0124] Example 3 proposes a method for producing a battery housing for energy storage, and the steps are basically the same as those of Example 2, except that:
[0125] In S1, the temperature is kept at 680°C for 2h.
[0126] In S2, the pressure is 2 MPa and the holding time is 40 s.
[0127] In S3, the three-stage heat treatment is as follows: the first stage heat treatment: cooling to 180°C at a cooling rate of 50°C / s, and homogenizing heat treatment at 180°C for 18h;
[0128] The second heat treatment: cooling to 0°C at a cooling rate of 100°C / s, then heating to 230°C at a heating rate of 28°C / s and keeping at this temperature for 40 min;
[0129] The third heat treatment: cooling to -150°C at a cooling rate of 180°C / s, then heating to 100°C at a heating rate of 125°C / s and keeping warm for 60 min.
[0130] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.9 mm.
[0131] Example 4
[0132] Example 4 proposes a method for producing a battery housing for energy storage, and the steps are basically the same as those of Example 2, except that:
[0133] In S1, the temperature was kept at 730°C for 5 hours.
[0134] In S2, the pressure is 4 MPa and the holding time is 60 s.
[0135] In S3, the three-stage heat treatment is as follows: the first stage heat treatment: cooling to 150°C at a cooling rate of 80°C / s, and homogenizing heat treatment at 150°C for 12h;
[0136] The second heat treatment: cooling to -5°C at a cooling rate of 50°C / s, then heating to 150°C at a heating rate of 26°C / s and keeping at this temperature for 80 min;
[0137] The third heat treatment: cool to -80°C at a cooling rate of 120°C / s, then heat to 180°C at a heating rate of 180°C / s and keep warm for 20 minutes.
[0138] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.6 mm.
[0139] Example 5
[0140] Example 5 proposes a method for producing a battery housing for energy storage, and the steps are basically the same as those of Example 2, except that:
[0141] In S2, the pressure is 5 MPa and the holding time is 10 s.
[0142] In S3, the three-stage heat treatment is as follows: the first stage heat treatment: cooling to 230°C at a cooling rate of 100°C / s, and homogenizing heat treatment at 230°C for 13h;
[0143] The second heat treatment: cooling to -10°C at a cooling rate of 100°C / s, then heating to 180°C at a heating rate of 25°C / s and keeping at this temperature for 70 min;
[0144] The third heat treatment: cool to -130°C at a cooling rate of 130°C / s, then heat to 120°C at a heating rate of 150°C / s and keep warm for 70 minutes.
[0145] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.63 mm.
[0146] Example 6
[0147] Example 6 proposes a method for producing a battery housing for energy storage, and the steps are basically the same as those of Example 2, except that:
[0148] In S4, the pretreated aluminum alloy shell is hot stamped at a temperature of 190°C for 15s; the cooling rate of quenching is 20°C / min.
[0149] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.83 mm.
[0150] Example 7
[0151] Example 7 proposes a method for producing a battery housing for energy storage, and the steps are basically the same as those of Example 2, except that:
[0152] In S4, the pretreated aluminum alloy shell is hot stamped at a temperature of 220°C for 10s; the cooling rate of quenching is 40°C / min.
[0153] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.62 mm.
[0154] Example 8
[0155] Example 8 proposes a method for producing a battery housing for energy storage, and the steps are basically the same as those of Example 2, except that:
[0156] In S4, the pretreated aluminum alloy shell is aged at a temperature of 120°C for 8 hours; the cooling rate of quenching is 50°C / s.
[0157] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.72 mm.
[0158] Example 9
[0159] Example 9 proposes a method for producing a battery housing for energy storage, and the steps are basically the same as those of Example 2, except that:
[0160] In S4, the aging treatment temperature is 180°C and the time is 20h; the cooling rate of quenching is 50°C / s.
[0161] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.71 mm.
[0162] Example 10
[0163] Example 10 proposes a method for producing a battery shell for energy storage. The steps are basically the same as those in Example 2, except that the aluminum alloy melt in S1 is composed of the following components in mass fractions: 83.19% aluminum, 13.38% lithium, 0.7% beryllium, 0.6% magnesium, 0.1% indium, 0.26% nickel, 0.4% silicon, 1.34% lanthanum and 0.03% boron.
[0164] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.62 mm.
[0165] Embodiment 11
[0166] Example 11 proposes a method for producing a battery shell for energy storage. The steps are basically the same as those in Example 2, except that the aluminum alloy melt in S1 is composed of the following components in mass fractions: 89.54% aluminum, 7% lithium, 0.6% beryllium, 0.5% magnesium, 0.11% indium, 0.1% nickel, 0.3% silicon, 1.82% lanthanum and 0.02% boron.
[0167] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.66 mm.
[0168] Example 12
[0169] Example 12 proposes a method for producing a battery shell for energy storage. The steps are basically the same as those of Example 2, except that the rare earth metal in the aluminum alloy melt is cerium.
[0170] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.65 mm.
[0171] Embodiment 13
[0172] Example 13 proposes a method for producing a battery shell for energy storage. The steps are basically the same as those of Example 2, except that the rare earth metals in the aluminum alloy melt are cerium and lanthanum, the mass fraction of cerium is 0.75%, and the mass fraction of lanthanum is 0.75%.
[0173] This embodiment also provides a battery shell for energy storage produced by the production method of this embodiment, and the wall thickness of the battery shell for energy storage is 0.61 mm.
[0174] Comparative Example 1
[0175] Comparative Example 1 proposes a method for producing a battery housing, and the steps are basically the same as those of Example 2, except that:
[0176] S2 does not apply additional pressure or maintain pressure.
[0177] In S3, the three-stage heat treatment is as follows: the first stage heat treatment: homogenization heat treatment at 120°C for 20h;
[0178] The second heat treatment: cooling to 10°C at a cooling rate of 40°C / s, then heating to 130°C at a heating rate of 20°C / s and keeping at this temperature for 10 min;
[0179] The third heat treatment: cooling to -50°C at a cooling rate of 100°C / s, then heating to 230°C at a heating rate of 100°C / s and keeping warm for 10 min.
[0180] This comparative example also provides a battery shell produced by the production method of this comparative example, and the wall thickness of the battery shell is 1.1 mm.
[0181] Comparative Example 2
[0182] Comparative Example 2 proposes a method for producing a battery casing, and the steps are basically the same as those of Example 2, except that:
[0183] S2 does not apply additional pressure or maintain pressure.
[0184] In S3, only the first stage of heat treatment is performed: homogenization heat treatment at 250°C for 10 hours.
[0185] This comparative example also provides a battery shell produced by the production method of this comparative example, and the wall thickness of the battery shell is 1.13 mm.
[0186] Comparative Example 3
[0187] Comparative Example 3 proposes a method for producing a battery shell, and the steps are basically the same as those of Example 2, except that:
[0188] In S4, the hot stamping temperature is 180°C and the time is 30s; the aging treatment temperature is 100°C and the time is 22h.
[0189] This comparative example also provides a battery shell produced by the production method of this comparative example, and the wall thickness of the battery shell is 0.98 mm.
[0190] Comparative Example 4
[0191] Comparative Example 4 proposes a method for producing a battery shell, and the steps are basically the same as those of Example 2, except that:
[0192] In S4, the hot stamping temperature is 250°C and the time is 3s; the aging treatment temperature is 200°C and the time is 22h.
[0193] This comparative example also provides a battery shell produced by the production method of this comparative example, and the wall thickness of the battery shell is 1.05 mm.
[0194] Comparative Example 5
[0195] Comparative Example 5 proposes an aluminum alloy plate for a battery case, composed of the following components in mass fractions: 0.6% manganese, 0.6% magnesium, 0.6% copper, 0.3% silicon, 0.5% iron, 0.01% titanium, 7 ppm boron, and the remainder is aluminum and unavoidable impurities.
[0196] The thickness of the aluminum alloy plate for the battery case is 0.9 mm.
[0197] Comparative Example 6
[0198] Comparative Example 6 proposes a battery case, wherein the material of the battery case is an aluminum alloy, and the aluminum alloy is composed of the following components in mass fractions:
[0199] 94.43% aluminum, 0.88% beryllium, 0.09% magnesium, 0.10% indium, 0.19% nickel, 0.39% silicon, 3.89% lanthanum and 0.03% boron.
[0200] The thickness of the battery case is 0.9 mm.
[0201] Comparative Example 7
[0202] Comparative Example 7 proposes a battery case, wherein the material of the battery case is an aluminum alloy, and the aluminum alloy is composed of the following components in mass fractions:
[0203] 87.61% aluminum, 10.84% lithium, 0.81% beryllium, 0.08% magnesium, 0.09% indium, 0.18% nickel, 0.36% silicon and 0.03% boron.
[0204] The thickness of the battery case is 0.9 mm.
[0205] Comparative Example 8
[0206] Comparative Example 8 proposes a battery case, wherein the material of the battery case is an aluminum alloy, and the aluminum alloy is composed of the following components in mass fractions:
[0207] 85.22% aluminum, 10.54% lithium, 0.08% magnesium, 0.09% indium, 0.18% nickel, 0.35% silicon, 3.51% lanthanum and 0.03% boron.
[0208] The thickness of the battery case is 0.9 mm.
[0209] In order to verify the advancement of a battery case for energy storage and a production method thereof provided in the embodiment of the present application, the yield strength (R el ); According to GB / T 10125 "Artificial atmosphere corrosion test salt spray test" the battery shells provided in the embodiments and comparative examples were subjected to acetic acid salt spray tests at room temperature (25°C) and high temperature (54°C), and according to GB / T 6461 "Rating of samples and test pieces of metal and other inorganic coatings on metal substrates after corrosion tests" the samples after the salt spray test were rated for appearance R A ; The results are shown in Table 1 below.
[0210] .
[0211] Note: In Table 1 above, the appearance rating R AIt is determined by the proportion of the defect area after the salt spray test: when A=0, R A is level 10; when 0<A≤0.1, R A is level 9; when 0.1<A≤0.25, R A is level 8; when 0.25<A≤0.5, R A is level 7; when 0.5<A≤1, R A is level 6; when 1<A≤2.5, R A is level 5; when 2.5<A≤5, R A is level 4; when 5<A≤10, R A is level 3; when 10<A≤25, R A is level 2; when 25<A≤50, R A is level 1; when 50<A, R A It is level 0.
[0212] From Table 1 above, we can at least draw the following conclusions:
[0213] (1) In the production method of the energy storage battery shell provided in the embodiment of the present application, the yield strength of the energy storage battery shell produced after the raw material is subjected to the pressure applied during casting, homogenization heat treatment and quenching cooling is above 191 MPa. The high strength can reduce the wall thickness of the battery shell, thereby reducing the energy density of the battery from the perspective of structural weight.
[0214] (2) The production method of the energy storage battery shell provided in the present application is that, in a rare gas atmosphere, it is not easy to introduce other non-metallic impurities or metal oxidation into the prepared aluminum alloy melt, thereby ensuring the purity of the aluminum alloy melt; the temperature is kept at 680°C~730°C for 2h~5h, so that the raw material components in the aluminum alloy melt are evenly mixed, the grains are refined, the fluidity of the aluminum alloy melt is improved, and the subsequent casting and molding of the aluminum alloy melt is facilitated.
[0215] (3) In the production method of the energy storage battery shell provided in the present application, beryllium, silicon, and rare earth metals in the aluminum alloy melt improve the fluidity of the aluminum alloy, making it easier for the aluminum alloy melt to fill the energy storage battery shell mold during the casting process, reducing the generation of defects such as pores and shrinkage holes, and making the liquid melt evenly distributed and then solidified.
[0216] (4) The production method of the energy storage battery shell provided in the present application applies pressure and maintains pressure when injecting the aluminum alloy melt into the energy storage battery shell mold, which can improve the density and strength of the energy storage battery shell.
[0217] (5) The production method of the energy storage battery shell provided in the present application adopts a three-stage heat treatment, wherein the second and third heat treatments adopt a process of rapid cooling to rapid heating followed by a short period of heat preservation, which can significantly refine the grains and enhance the mechanical properties (tensile strength, ductility and toughness) of the aluminum alloy; the heat treatment can also form a metal oxide film on the surface of the shell, thereby improving the corrosion resistance of the energy storage battery shell.
[0218] (6) The production method of the energy storage battery shell provided in the present application can further refine the grain size of the aluminum alloy shell by hot stamping, thereby minimizing the weight of the energy storage battery shell product while maintaining the performance of the energy storage battery shell product, thereby improving the energy density of the battery from the perspective of the battery shell structure.
[0219] (7) In the production method of the energy storage battery shell provided in the present application, aging treatment can promote the formation and stabilization of the hard phase in the aluminum alloy, thereby improving the strength and hardness of the material.
[0220] (8) The energy storage battery shell produced by the production method of the energy storage battery shell provided in the present application has high mechanical properties, thermal stability and corrosion resistance.
[0221] (9) The energy storage battery shell provided in this application contains lightweight metal elements such as beryllium, magnesium, and indium in the aluminum alloy, which reduces the weight of the battery shell, and its grain structure is dense, with a grain size of less than 50 μm. When the wall thickness of the energy storage battery shell is less than 1 mm, its thermal stability, strength, and toughness still meet the requirements.
[0222] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for producing a battery housing for energy storage, characterized in that: The steps include: S1. In a rare gas atmosphere, a molten aluminum alloy raw material is mixed and kept at 680°C to 730°C for 2h to 5h to obtain an aluminum alloy melt, wherein the aluminum alloy melt is composed of the following components by mass fraction: 7% to 15% lithium, 0.6% to 0.8% beryllium, 0.5% to 0.8% magnesium, 0.08% to 0.11% indium, 0.09% to 0.2% nickel, 0.2% to 0.4% silicon, 1.2% to 2% rare earth metal, 0.02% to 0.03% boron, and the balance is aluminum and unavoidable impurities; S2. At a pressure of 2MPa~5MPa, the aluminum alloy melt is injected into the energy storage battery housing mold and maintained at a pressure of 10s~60s; S3. The aluminum alloy shell after pressure maintenance is subjected to three-stage heat treatment to obtain a pretreated aluminum alloy shell; The three-stage heat treatment includes: The first stage of heat treatment: cooling down to 150℃~230℃ at a cooling rate of 50℃ / s~100℃ / s; homogenization heat treatment for 12h~24h; The second heat treatment: cool to -10°C~0°C at a cooling rate of 50°C / s~100°C / s, then heat to 150°C~230°C at a heating rate of 25°C / s~30°C / s and keep warm for 20min~80min; The third heat treatment: cooling to -150℃~-80℃ at a cooling rate of 120℃ / s~180℃ / s, then heating to 100℃~180℃ at a heating rate of 125℃ / s~180℃ / s and keeping warm for 20min~80min; S4. The pretreated aluminum alloy shell is hot stamped and then quenched and cooled to obtain a battery shell for energy storage; The pre-treated aluminum alloy shell is subjected to aging treatment after hot stamping, the temperature is 120° C. to 180° C., and the time is 8 h to 20 h; In the hot stamping step, the temperature is 190° C. to 220° C., and the holding time is 5 s to 20 s.
2. The method for producing a battery casing for energy storage according to claim 1, characterized in that: The rare gas is at least one of helium, neon and argon.
3. The method for producing a battery casing for energy storage according to claim 2, characterized in that: In the hot stamping step, the hot stamping is performed once or more.
4. The method for producing a battery casing for energy storage according to claim 1, characterized in that: The rare earth metal includes at least one of lanthanum and cerium.
5. A battery housing for energy storage, characterized in that: The battery shell is produced by the production method for energy storage battery shell according to any one of claims 1 to 4.
Citation Information
Patent Citations
Forming method for light metal plate
CN105369072A
Production method of battery shell for energy storage and battery shell for energy storage
CN117340030A